Asociación entre anemia y mortalidad cardiovascular a los 30 días del ingreso en pacientes admitidos en emergencia por insuficiencia cardiaca descompensada - Armas Flores, Cristian David (2017)
Objective: To determine if there is an association between anemia and cardiovascular mortality within 30 days after the admission, in patients admitted in emergency service with decompensated heart failure. Material and method: A retrospective, case-control, retrospective study was conducted, which included 132 patients admitted at the emergency, respecting the inclusion and exclusion criteria. The ratio of cases and controls was 1:3 and data were obtained from clinical records in level III hospitals with similar populations over 5 years. Pearson's Chi-square test was used to determine the association. Results and conclusions: In both groups the main age was 72 years and the female sex was greater in the control group (62%). Anemia was found in 64% of cases and 39% of controls. The association between anemia and cardiovascular mortality was determined in patients admitted with decompensated heart failure (OR: 2.69, 95% CI, 1.191-6.087, p = 0.015) after adjustment for traditional confounders (left ventricular ejection fraction, age, sex and chronic kidney disease). Anemia proved to be a very common pathology in patients with exacerbation of heart failure and also is a mortality factor